Protein expression of CYP1A1, CYP1B1, ALDH1A1, and ALDH2 in young patients with oral squamous cell carcinoma - Kaminagakura, E. [UNESP]; Caris, A. [UNESP]; Coutinho-Camillo, C.; Soares, F. A.; Takahama-Júnior, A.; Kowalski, L. P. (Elsevier, 2016)
The purpose of this study was to evaluate the expression of the enzymes involved in the biotransformation of tobacco and alcohol. A study group of 41 young patients (≤40 years old) with oral squamous cell carcinoma (OSCC) was compared to 59 control subjects (≥50 years old) with tumours of similar clinical stages and topographies. The immunohistochemical expression of CYP1A1, CYP1B1, ALDH1A1, and ALDH2 was evaluated using the tissue microarray technique. There was a predominance of males, smokers, and alcohol drinkers in both groups. Most tumours were located in the tongue (43.9% vs. 50.8%), were well-differentiated (63.4% vs. 56.6%), and were in clinical stages III or IV (80.5% vs. 78.0%). No difference was observed in the expression of CYP1A1, ALDH1A1, or ALDH2 between the two groups. CYP1A1 and ALDH2 protein expression had no influence on the prognosis. The immunoexpression of CYP1B1 was significantly higher in the control group than in the young group (P < 0.001). The 5-year relapse-free survival was better in patients with CYP1B1 overexpression vs. protein underexpression (64% vs. 25%; P < 0.05), regardless of age. ALDH1A1 expression improved relapse-free survival in young patients. These results suggest a lower risk of recurrence with increased metabolism of carcinogens by CYP1B1. Further studies involving other genes and proteins are necessary to complement the results of this research.
Keywords: aldehyde dehydrogenase; ALDH; CYP; cytochrome P450; oral cancer; squamous cell carcinoma; young age